2016
DOI: 10.5032/jae.2016.02001
|View full text |Cite
|
Sign up to set email alerts
|

Student-to-Student Interaction in Distance Education Classes: What Do Graduate Students Want?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
0
5
0
8
Order By: Relevance
“…Several factors were reported as determinants of student interaction in online learning. Learners' style, instructor teaching style, course content, course design and length, instructional style, class size and support system are examples of such determinants (Orellana, 2009;Su et al, 2005;Song et al, 2019;Moore et al, 2016, Roddy et al, 2017. Bernard et al (2009) reported the importance of three types of interaction in distance and online-learning: Instructor-students, students-students and student-content interaction (Abrami et al, 2011;Kuo et al, 2014b).…”
Section: Ijem 353mentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors were reported as determinants of student interaction in online learning. Learners' style, instructor teaching style, course content, course design and length, instructional style, class size and support system are examples of such determinants (Orellana, 2009;Su et al, 2005;Song et al, 2019;Moore et al, 2016, Roddy et al, 2017. Bernard et al (2009) reported the importance of three types of interaction in distance and online-learning: Instructor-students, students-students and student-content interaction (Abrami et al, 2011;Kuo et al, 2014b).…”
Section: Ijem 353mentioning
confidence: 99%
“…Bernard et al (2009) reported the importance of three types of interaction in distance and online-learning: Instructor-students, students-students and student-content interaction (Abrami et al, 2011;Kuo et al, 2014b). A survey of 220 students who completed one or more distance learning courses found that the majority of the students did not like student-tostudent interaction and such result still valid with a subgroup analysis considered age, gender, work status, personality type and student distance as full or part-time (Moore et al, 2016). Kuo (2010) found student-instructor and student-content acts as major predictors for satisfaction in online courses.…”
Section: Ijem 353mentioning
confidence: 99%
“…Pada pembelajaran online terjadi interaksi antara peserta didik dengan peserta didik lainnya (learner-learner), peserta didik dengan pengajar (learner-instructor), interaksi peserta didik dengan materi yang disebut (learner-content) (Moore, Warner, & Jones, 2016). Selain itu juga terjadi interaksi antara peserta didik dan pengajar dengan sistem (Marcus, 2006).…”
Section: Pendahuluanunclassified
“…Student-student interactions may occur between one student and other student or with many students in group settings, with/without the real-time presence of an instructor; various studies demonstrate that this form of interaction is an important experience and learning resource (Su et al, 2005). Empirical evidence indicates that students essentially prefer student-student interactions, irrespective of the delivery mode (G. E. Moore et al, 2016). According to M. G. Moore (1989, p. 2), student-content interaction is referred to as "the process of intellectually interacting with content that results in changes in the learner's understanding, the learner's perspective, or the cognitive structures of the learner's mind.…”
Section: Communication Competencymentioning
confidence: 99%